Workshop on Graphic Anthropology - Ramos, M. (Faculty Seminar in Anthropology - Institut fuer Ethnologie - Universitat Hamburg, 2017)
A Graphic Anhropology Workshop, for students of the Institute of Ethnology of the University of Hamburg, 14 June 2017